منهج القرآن الكريم في تأصيل سد الذرائع-دراسة تطبيقية مع نماذج معاصرة - - لينة كيرد; حورية قرزو; -أ.د/ عامر فاطنة (جامعة عمار ثليجي الاغواط, 2023)
الحمددد لله رب العدددالمين والصددد والسددد م علددد نبيددد الكدددريم وبعددد : فددد ن بحثندددا الموسدددوم بددد : مننن ال رآننننكري رآينننكيل سنننا ذراننني ننن ك رآننن كر - كر ننن ذطبينيننن مننن مننن -هددد مدددةكر مق مة لنيل شها الماستر ف الفق المقارن وأصول اشتملت عل مق مة وفصلين وخاتمة. اشددددتمل الفصددددل ا ول ث ثددددة مباحدددد فكددددان فدددد المبحدددد ا ول التعريدددد بالمصدددد لحات البحدددد واحتدددو المبحدددد الثدددان علددد حعيددددة وألسدددام سدددد الددددةرا و ت دددمن المبحدددد الثالدددد مدد خل لدد علددم أصددول الفقدد وع لتدد بسدد الددةرا ومددنها القددرتن الكدديم فدد ت صدديلها. ثددم كددان العمددددل فدددد الفصددددل الثددددان مددددن ث ثددددة مباحدددد ت بيقيددددة حيدددد تناولنددددا فيهددددا مسددددا ل مسددددتع ومعاصر وف الخاتمة ةكر أهم النتا ا الت توصلنا ليها. Summary: Praise be to God, Lord of the worlds, and prayers and peace be upon His noble Prophet, and after: Our research, which is tagged with: The Holy Qur’an Approach in the Rooting of Sidr Al-Dhara’i - an applied study with models - is a memorandum submitted for obtaining a master’s degree in comparative jurisprudence and its principles, and it included an introduction, two chapters, and a conclusion. The first chapter included three sections. The first section included the definition of the research terminology. The second section contained the authoritative and sections of bridging pretexts. The third topic included an introduction to the science of jurisprudence and its relationship to bridging pretexts and the approach of the Holy Qur’an in its rooting. Then the work was in the second chapter of three applied investigations, in which we dealt with emerging and contemporary issues, and in the conclusion he mentioned the most important results that we rea